Pusat Pelatihan Bola Basket Di Pekanbaru Dengan Pendekatan Arsitektur Ekspresionis - Pahlevi, Said Iqrak; Hidayat, Wahyu; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pekanbaru has the potential that can be developed through the field of basketball. However, there is a lack of attention from the government so that this potential is not developed well. Thus in need of proper containers for enthusiasts to make proud of Pekanbaru. In building a container is also paying attention to facilities that follow the standards in terms of architectural convenience. The research method used through field survey, documentation, and analysis of the lines on the basketball. The results of this research describes how the application of basketball can be applied in expressionist architecture by applying characteristics lines on Expressionist architectural elements, such as the shape of the building, circulation, structure, material, as well as color. This research can also confirm that the Basketball Training Center can be used as inspiration and applied to the design of the building of expression which followed expressionist architecture elements of the element itself. Keywords: Architecture, Pekanbaru, Basketball, Expressionist Architecture